2017
DOI: 10.1186/s12885-017-3180-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating young women’s motivations to engage in early mammography screening in Switzerland: results of a cross-sectional study

Abstract: BackgroundThe scientific and public debate concerning organized mammography screening is unprecedentedly strong. With research evidence concerning its efficacy being ambiguous, the recommendations pertaining to the age-thresholds for program inclusion vary between – and even within – countries. Data shows that young women who are not yet eligible for systematic screening, have opportunistic mammograms relatively often and, moreover, want to be included in organized programs. Yet, to date, little is known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 33 publications
1
23
0
2
Order By: Relevance
“…Compared to women with high educational level, those with low educational level underwent This was surprising, as most previous studies did not reveal any positive or negative association of numeric and comparative risk perception with participation in MS [10,12,16,20]. Labrie and colleagues [24] suggested that fear of breast cancer increased the perception of personal risk among women aged 30 -49 years. A recent study performed in Malta suggested that non-adherence to organized MS programs was associated with fear [25].…”
Section: Resultsmentioning
confidence: 90%
“…Compared to women with high educational level, those with low educational level underwent This was surprising, as most previous studies did not reveal any positive or negative association of numeric and comparative risk perception with participation in MS [10,12,16,20]. Labrie and colleagues [24] suggested that fear of breast cancer increased the perception of personal risk among women aged 30 -49 years. A recent study performed in Malta suggested that non-adherence to organized MS programs was associated with fear [25].…”
Section: Resultsmentioning
confidence: 90%
“…The reasons why women chose to opt for private mammography rather than to the organized programme are not yet fully understood. This may be due to women seeking BS at a younger age (30–49) as a precautionary measure [ 20 ] and continue to sustain early detection practices in this way. Evidence from the U.S. National Health Interview Survey revealed that 29% of women aged 30–39 have undergone mammography [ 73 ] while data from the 2010 Behavioural Risk Factor Surveillance Study showed that 83% of women aged 40–49 have had BS [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the U.S. National Health Interview Survey revealed that 29% of women aged 30–39 have undergone mammography [ 73 ] while data from the 2010 Behavioural Risk Factor Surveillance Study showed that 83% of women aged 40–49 have had BS [ 74 ]. Hence, public health strategies and wide media coverage directed at convincing older women to engage in BS may arouse a positive attitude among younger age groups towards early detection practices [ 75 , 76 ] or may induce anxiety and fear of BC and mortality, motivating younger women, particular those aged 40–49, to engage in mammography screening [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations